PENGARUH SIKAP DAN PERAN ORANG TUA TERHADAP PERGESERAN BAHASA LUWU DI KALANGAN ANAK-ANAK PADA MASYARAKAT LUWU KOTA PALOPO - Jumhariah Djamareng; Jufriadi Jufriadi (Palita: Journal of Social Religion Research, 2016)
This study aims to describe the condition of Luwu language shift among children in Palopo city. Furthermore, it was seen whether the attitude factor and the role of parents affect the use of Luwunese. To answer these issues, the researchers involved the societies of Palopo who live in the districts of Wara, East Wara, Bara, and Tellu Wanua as the population of this study. Then, this study involved 120 samples consisting of; 1) 60 children around 6 12 year old (primary school age) in which 10 children were chosen from each district; and 2) 60 older people (30-50 years old, married). Data collecting techniques were in forms of observation, questionnaires and interviews through note taking and recording as the research instruments. The findings showed that the language shift occurred among children in Palopo city based on the data percentage analysis obtained from the questionnaires. The use of Luwunese by parents was the roles of parents in providing significant influences on the language shift occurring in children shown by the percentage calculation where almost the respondents showed a lack of Luwunese use by children and parents in their family interactions. The parents positive attitude towards the use of Luwunese indicated by the questionnaire percentage had no impact on Luwunese preservation; whereas, the Luwunese shift occurred in Palopo city.